Functional Outcome of Arthroscopic Single Bundle Anterior Cruciate Ligament Reconstruction (ACLR) using Hamstring Auto Graft (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of arthroscopic single-bundle Anterior Cruciate Ligament Reconstruction (ACLR ) using Hamstring auto graft in patients with complete Anterior Cruciate Ligament (ACL) rupture.Methods: This descriptive study was conducted in Liaquat National Hospital, Karachi from 20th March 2016 to 20th March 2021.All adults patients with ACL tear fulfilling the inclusion criteria were treated arthroscopically with single bundle ACLR using Hamstring auto graft. Functional outcome at two years were assessed with International Knee Documentation Committee (IKDC) scoring system and compared with pre operative value. P value was calculated with Chi-square test and Independent Sample-t test. P value